Telomere length as a marker of cellular aging is associated with prevalence and progression of metabolic syndrome - Révész, Dóra; Milaneschi, Yuri; Verhoeven, Josine E; Penninx, Brenda W J H (The journal of clinical endocrinology and metabolism, 2014)
Metabolic syndrome (MetS) clusters risk factors for age-related conditions including cardiovascular disease and diabetes. Shorter telomere length (TL), a cellular marker for biological age, may predict an individual's deteriorating metabolic condition. We examined whether shorter baseline TL is associated with a worse metabolic profile and with less favorable trajectories of MetS components over a 6-year follow-up. PARTICIPANTS were part of The Netherlands Study of Depression and Anxiety, an ongoing prospective cohort study with 6-year follow-up. This study included 2848 participants age 18-65 years. Baseline TL from leukocytes was determined using qPCR and MetS components (waist circumference, triglycerides, high-density lipoprotein [HDL] cholesterol, systolic blood pressure, and fasting glucose) were determined at baseline, and after 2 and 6 years. Cross-sectional and longitudinal analyses were adjusted for relevant sociodemographic, lifestyle, and health factors. Shorter baseline TL was cross-sectionally associated with HDL (β = -0.016, SE = 0.008, P = .05), waist circumference (β = 0.647, SE = 0.238, P = .007), triglycerides (β = 0.038, SE = 0.009, P < .001), and fasting glucose (β = 0.011, SE = 0.003, P < .001), as well as with the total number of MetS components (β = 0.075, SE = 0.023, P = .001) and the presence of MetS (OR = 1.19; 95% CI, 1.07-1.33; P = .002). Although baseline differences progressively reduced over time, shorter baseline TL was still significantly associated with unfavorable scores of most MetS components at the 2- or 6-year follow-up. Cellular aging, as assessed by TL, is associated with a higher metabolic risk profile, which remains unfavorable even after a period of 6 years. These findings suggest that cellular aging might play a role in the onset of various aging-related somatic diseases via its effect on metabolic alterations.